CHEMICAL COMPOSITION AND INSTRUMENTAL QUALITY OF BOVINE, LLAMA (LAMA GLAMA) AND HORSE MEAT UNDER AN EXTENSIVE PRODUCTION SYSTEM - Mamani-Linares, Lindon W. (2011)
This study compared the chemical composition and instrumental meat quality of bovine, llama and horse from animals finished under grazing systems. The bovines (n=31), llamas (n=21) and horses (n=27) were slaughtered using Chilean standard procedures. Carcasses were stored for 24 h in a cold room (4 ºC). The Longissimus lumborum muscle (LL) was collected for determining the chemical composition, cholesterol, collagen content, pH, colour (L*, a*, b*, H*, C*), water holding capacity (WHC) and Warner–Bratzler shear-force (WBSF). Llama meat had higher levels of protein and total collagen (p<0.05), and lower level of fat and cholesterol (p<0.05) than bovine and horse meat. No statistical differences were found in moisture and ash percentages between species. The L* (lightness) and b* (yellowness) values of llama LL were higher (p<0.05) than those in the bovine and horse, while the values of a* (redness) and C* (chroma) of LL bovine were greater (p<0.05). The pH in LL bovine meat was higher than in llama (p<0.05). WHC, total cooking loss and evaporation cooking loss were similar, while WBSF in horse was greater (p<0.05).